The Effect of Ads Personalization on TikTok Shop Users' Purchase Intent: The Role of Trust Mediation and Moderation of Data Privacy Concerns - Ibrahim Bafadal; Danang Ary Dewangga; Ratih Amelia; Dhiyan Septa Wihara (Majapahit Journal of Islamic Finance and Management, 2026)
The rapid growth of social commerce has transformed digital marketing strategies from mass-oriented approaches into more personalized and data-driven practices. As one of the leading social commerce platforms, TikTok Shop utilizes ads personalization to deliver product recommendations tailored to users’ preferences and online behaviors. However, the effectiveness of personalized advertising in stimulating purchase intention is not solely determined by the relevance of information provided but is also influenced by users’ trust in the platform and their concerns regarding personal data privacy. This study aims to examine the effect of ads personalization on TikTok Shop users’ purchase intention, with trust acting as a mediating variable and data privacy concerns serving as an influential factor in consumer purchasing behavior within a digital commerce environment. This research employed a quantitative approach using a survey method involving 102 TikTok Shop users selected through purposive sampling. Data were collected through an online questionnaire and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 4 software. The analysis included assessments of convergent validity, discriminant validity, reliability, and structural model evaluation to test the proposed hypotheses. The findings indicate that all constructs satisfied the required validity and reliability criteria. Ads personalization was found to have a positive effect on both trust and purchase intention among TikTok Shop users. Trust also demonstrated a positive influence on purchase intention and acted as a mediating variable in the relationship between ads personalization and purchase intention. Furthermore, data privacy concerns were identified as an important factor influencing consumers’ purchasing behavior within the social commerce ecosystem. The coefficient of determination revealed that the model explained 49.2% of the variance in trust and 71.9% of the variance in purchase intention. This study concludes that the effectiveness of personalized advertising in enhancing purchase intention is determined not only by the platform’s ability to provide relevant recommendations but also by its capacity to build user trust and manage perceived privacy risks effectively. These findings contribute to the development of digital marketing literature and provide practical implications for businesses in designing effective marketing strategies on TikTok Shop.